PENGARUH PUPUK KANDANG DOMBA TERHADAP SERAPAN NITROGEN (N) TANAMAN SELADA (Lactuca sativa L.) PADA ENTISOLS LEMBAH PALU - Prasetyo, Harry Dwi; Pata’dungan, Yosep S.; Isrun, Isrun (AGROTEKBIS, 2018)
This study aims to determine the effect of sheep manure to the increased uptake of nitrogen (N) lettuce (Lactuca sativa L.) in soil Entisols Palu valley. The study begins with the soil sampling in the Loluvillage, District Sigi Biromaru, Sigi, at a depth of 20 cm. The method used in this study was prepared using a randomized block design with four levels of dose and repeated 3 times to obtain 12 units of trial. Four levels of a treatment are: d1 = Without manure of sheep, d2 = Manure sheep dose of 15 t / ha (Equivalent to 20 g / polybag), d3 = Manure sheep dose of 30 t / ha (equivalent 40 g/polybag), d4 = sheep manure dose 45 t/ha (Equivalent to 60 g / polybag). Parameters observed that C-Organic, pH, N-Total, Concentration N, Plant Dry Weight and Uptake of N. From the results of research on the effect of sheep dung on lettuce crop nitrogen uptake levels achieved the highest N uptake in the manure of sheep at a dose of 45 t ha-1 every analysis done on the study. Increasing doses of sheep manure is always followed by increasing soil pH, organic C, N-total, dry weight of the plant, as well as the N concentration in plant tissue and crop N uptake in lettuce.